إدارة الموارد البشرية بالجودة الشاملة في المكتبات ومراكز المعلومات: الأسس؛ المعايير والمتطلبات - بوعافية, د/ السعيد (Sciences humaines, 2014)
لقد أصبح العنصر البشري مؤخرا أهم مورد من بين موارد المكتبات ومراكز المعلومات، كما أن إدارة وتسيير الموارد البشرية أصبحت تمثل مهمة ومسؤولية جد صعبة، هذا لأن تحقيق المؤسسة التوثيقية لأهدافها وأبرزها رفع الإنتاجية وتحسين أدائها مرتبط بشكل كبير برفع إنتاجية وتحسين أداء الأفراد العاملين بها. وتهدف الورقة إلى تقديم الإطار النظري حول الإدارة الحديثة للمكتبات ومراكز المعلومات في ظل عالم متغير، والتعرف على الأساليب الحديثة لإدارة الموارد البشرية التي يمكن الإفادة منها في مكتباتنا، ومنها إدارة الجودة الشاملة وبالتالي محاولة ضبط الصورة الحديثة للموارد البشرية العاملة في المكتبات وفق معايير الجودة الشاملة سعيا لتطوير الأداء وإكتساب ثقافة المواجهة مستقبلا.   The human race has recently  become the most important resource of the resources of Libraries and Information Centers, the Department of Human Resources Management has become a very difficult task and responsibility, this because of the institution documenting their objectives, the most prominent of which is the raising of productivity and improve their performance is largely to raise productivity and improve the performance of its personnel, The paper aims to provide theoretical framework on modern management Libraries and Information Centers in a changing world, and identify methods to modern human resources management, which could benefit in the libraries, including the management of comprehensive quality and thus attempt to adjust the picture modern human resources working in libraries according to quality standards in order to develop comprehensive performance and gain a culture of confrontation in the future.